2009
DOI: 10.1111/j.1558-5646.2008.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Predation's Role in Repeated Phenotypic and Genetic Divergence of Armor in Threespine Stickleback

Abstract: Predator-driven divergent selection may cause differentiation in defensive armor in threespine stickleback: (1) predatory fish and birds favor robust armor, whereas (2) predaceous aquatic insects favor armor reduction. Although (1) is well established, no direct experimental evidence exists for (2). I examined the phenotypic and genetic consequences of insect predation using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 72 publications
(132 reference statements)
2
158
3
Order By: Relevance
“…Eda genotype frequencies changed strongly but irregularly through two generations in experimental populations (Barrett et al 2008), but in a lake population founded by oceanic stickleback, the frequency of low morphs (and presumably Eda L alleles) increased rapidly among each of several consecutive generations, reaching 75% within about ten generations (Bell et al 2004; see also Francis et al 1985;Klepaker 1993;Vamosi 2006). Reimchen (2000) presented evidence that low-plated stickleback are more likely than complete morphs to avoid capture by predatory fishes in fresh water, and Marchinko (2009) presented evidence that low morphs experience lower rates of insect predation. Marchinko and Schluter (2007) also found that low morphs grow much faster in fresh water than completes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eda genotype frequencies changed strongly but irregularly through two generations in experimental populations (Barrett et al 2008), but in a lake population founded by oceanic stickleback, the frequency of low morphs (and presumably Eda L alleles) increased rapidly among each of several consecutive generations, reaching 75% within about ten generations (Bell et al 2004; see also Francis et al 1985;Klepaker 1993;Vamosi 2006). Reimchen (2000) presented evidence that low-plated stickleback are more likely than complete morphs to avoid capture by predatory fishes in fresh water, and Marchinko (2009) presented evidence that low morphs experience lower rates of insect predation. Marchinko and Schluter (2007) also found that low morphs grow much faster in fresh water than completes.…”
Section: Discussionmentioning
confidence: 99%
“…Rare Eda C alleles in the generally low-plated resident Mud Lake population should nearly all be Eda L /Eda C heterozygotes, which would be recognizable as complete or partial morphs. Although they should have reduced fitness in freshwater (Reimchen 2000;Marchinko and Schluter 2007;Barrett et al 2009a;Marchinko 2009), they might still be present among adult and larger juvenile fish, in which they can be reliably scored (Bell 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype axis is scaled differently in the two panels but is otherwise comparable chances of survival after escape) (Reimchen 1992(Reimchen , 2000. However, armor is costly to produce (Marchinko and Schluter 2007;Barrett et al 2009) and might even be a liability inshore where insects are the main killers, possibly by making stickleback easier to grasp (Reimchen 1980;Marchinko 2009). Life history differences may also represent adaptations to contrasting mortality factors.…”
Section: Wider Impactsmentioning
confidence: 99%
“…Sticklebacks show considerable morphological and behavioural variation both within and between populations. Populations facing high levels of predation differ from predator-free populations in morphology (Bell and Foster 1994;Marchinko 2009). Differences in morphology are shown to have arisen by selective predation on more vulnerable phenotypes (e.g., Reimchen 1980Reimchen , 2000, and are thus reflecting genetic differences.…”
Section: Introductionmentioning
confidence: 99%